Skill-Biased Management: Evidence from Manufacturing Firms. Issue 628 (24th January 2020) - Feng, Andy; Valero, Anna
Abstract: This article investigates the link between management practices and workforce skills in manufacturing firms, exploiting geographical variation in the supply of human capital. Skills measures are constructed using newly compiled data on universities and regional labour markets across 19 countries. Consistent with management practices being complementary with skills, we show that firms further away from universities employ fewer skilled workers and are worse managed, even after controlling for a rich set of observables and fixed effects. Analysis using regional skill premia suggests that variation in the price of skill drives these relationships.